2022
DOI: 10.3390/fermentation8050228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ammoniated and/or Basidiomycete White-Rot Fungi Treatment on Rice Straw Proximate Composition, Cell Wall Component, and In Vitro Rumen Fermentation Characteristics

Abstract: Various pretreatments are employed to increase the utilization of rice straw as a ruminant feed ingredient to minimize its negative environmental impact. However, an efficient alternative is still needed. The purpose of this study was to evaluate the ability of ammonia and/or white-rot fungi (Pleurotus ostreatus) to degrade lignin, increase the nutritional value, and enhance the rumen fermentability of rice straw. Rice straw was treated with ammonia and/or basidiomycete white-rot fungi (P. ostreatus) with untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
(89 reference statements)
1
6
0
Order By: Relevance
“…47 The high production of propionate by steam and lime pasteurized straw also demonstrates better fermentation of fiber, resulting in a shift in the microbial population or in the metabolic pathways that promote the synthesis of propionate. Increase in the production of VFAs and a decrease in acetate-to-propionate ratio in P. ostreatus treated rice straw is reported by Datsomor et al 48 Considering the findings of previous studies, which showed that wheat straw naturally contains AFB 1 less than 4 ppb, 49 and the findings of Jackson and Pryor, 50 who reported that P. ostreatus can degrade up to 94% of AFB 1 in homogenized whole corn, AFB 1 production during the P. ostreatus treatment was less likely. The concentration of AFB 1 in fungus-treated straw was much lower than the threshold level of AFB 1 in animal feed (20 ppb) recommended by the EU.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…47 The high production of propionate by steam and lime pasteurized straw also demonstrates better fermentation of fiber, resulting in a shift in the microbial population or in the metabolic pathways that promote the synthesis of propionate. Increase in the production of VFAs and a decrease in acetate-to-propionate ratio in P. ostreatus treated rice straw is reported by Datsomor et al 48 Considering the findings of previous studies, which showed that wheat straw naturally contains AFB 1 less than 4 ppb, 49 and the findings of Jackson and Pryor, 50 who reported that P. ostreatus can degrade up to 94% of AFB 1 in homogenized whole corn, AFB 1 production during the P. ostreatus treatment was less likely. The concentration of AFB 1 in fungus-treated straw was much lower than the threshold level of AFB 1 in animal feed (20 ppb) recommended by the EU.…”
Section: Discussionmentioning
confidence: 59%
“…The high production of propionate by steam and lime pasteurized straw also demonstrates better fermentation of fiber, resulting in a shift in the microbial population or in the metabolic pathways that promote the synthesis of propionate. Increase in the production of VFAs and a decrease in acetate‐to‐propionate ratio in P. ostreatus treated rice straw is reported by Datsomor et al 48 …”
Section: Discussionmentioning
confidence: 63%
“…The analysis of the chemical composition of the fresh unfermented alperujo obtained from different industrial of extraction of olive oil using a two-stage centrifugation system in Tunisia is shown in Table 1 . This semi-solid waste is characterized by a high content of lignocellulosic compounds similar to those of cereal straw widely used in rumen feeding, but with a higher content of lignin, protein, and EE (Datsomor et al 2022 ; Sufyan et al 2022 ). The chemical composition of this semi-solid waste was comparable to that found by Marcos et al ( 2019 ) in alperujo from Spain.…”
Section: Resultsmentioning
confidence: 99%
“…Ammoniation is conducted to generate ammonolysis reaction in crop straw by using ammonia-containing chemicals, such as liquid ammonia, urea, and ammonium bicarbonate ( Yu et al, 2015 ; Doğan and Hayırlı, 2022 ). Through ammoniation, ester bonds between lignin and polysaccharide in crop straw can be damaged, making straw more decomposable in soil ( Datsomor et al, 2022 ). Up to now, although key parameters, including temperature, moisture level, treatment period, and so on, have been optimized, ammonia emission in ammoniation process is still a serious challenge ( Cloete and Kritzinger, 1984 ; Ma et al, 2020c ).…”
Section: Integration Of Cyanobacteria-based Ammonia Absorption With A...mentioning
confidence: 99%